Changing Competences: Flipped Classroom and the Challenges in Teacher Training - Wolff, Bianca (Social Education Research, 2025)
The flipped classroom teaching concept is considered innovative because it changes the traditional teaching structure and creates more space for active learning processes. At the same time, it also requires other competences from teachers. In this article, a survey is conducted with 18 student teachers in mathematics in order to record their views on the necessary competences and challenges of the flipped classroom concept and to derive recommendations for teacher training. The aim of this study is to analyse the self-assessment of student teachers with regard to their future role and the competences required for the flipped classroom. Essentially, this shows that the student teachers have a positive attitude towards the flipped classroom concept. The students emphasise the need for assessment and media skills among teachers as well as the challenges posed by the increased planning effort and communication requirements towards parents and school management. Although the results are limited due to the small and unbalanced sample, they offer approaches for teacher training in order to better prepare future teachers for innovative teaching methods. There is a call for teachers to act more as learning facilitators and in particular to develop technological, media didactic and assessment skills. This exploratory study emphasises the need for further research and curriculum adaptation in teacher education.